Gastric myeloid sarcoma: A case report - Rioja, P (2021)
Background: Myeloid sarcoma (MS) is a rare hematologic malignancy defined as an extramedullary tumor of immature granulocytic cells. It can occur as primary or de novo and be associated with myelodysplasia or myeloproliferative neoplasms. The most frequent locations are the skin, lymph nodes and bones. The case of a patient with a diagnosis of primary granulocytic de novo gastric MS is reported. Case summary: A 19-year-old female patient with MS, whose abdominal computed tomography showed a bulky tumor of 16.5 cm in the gastric chamber with infiltration in the retroperitoneal, pancreatic and bile duct region; the histological study showed gastric mucosa diffusely infiltrated by mononucleated cells and the immunohistochemistry expressed myeloperoxidase. After receiving induction chemotherapy based on the 3 + 7 regimen (daunorubicin/cytarabine), the patient developed severe hematological toxicity and neutropenic typhlitis which required a prolonged medical treatment. She presented a rapid disease progression. Although she received supportive treatment, the patient died. Conclusion: Gastric primary de novo MS is a rare and aggressive course neoplasm, fostering knowledge is very important to decide its management and to promote more approaches focused on understanding this pathology and its particularities in our population.